Incidence of Atrioventricular Blocks and its Association with In-Hospital Mortality and Morbidity in Patients with Coronavirus Disease 2019. Issue 4 (April 2022) - Lao, Nicole; Lim, Joseph; Bashir, Hanad; Mahalwar, Gauranga; Adebolu, Olayinka; Mangira, Caroline; Courson, Jeffrey; Hegde, Vinayak
Highlights: Cardiovascular sequelae of COVID-19 are increasingly recognized. Arrhythmias, particularly new onset heart blocks can occur in COVID-19 patients. New onset heart blocks were not associated with increase in morbidity and mortality. Heart blocks are likely a consequence of systemic illness. New onset heart blocks are not solely the direct effects of COVID-19 infection. Abstract: Background: Cardiovascular sequelae of coronavirus disease 2019 (COVID-19) infection have been explored by clinicians and researchers all over the world. Objective: The purpose of this study was to evaluate the incidence of atrioventricular block (AV) in patients hospitalized for COVID-19 and its association between in-hospital morbidity and mortality. Methods: In-hospital electrocardiograms (ECGs) of 438 patients were compared with their prior or baseline ECGs to ascertain the development of new onset AV block. Patients who developed new AV blocks were then followed at 30 and 90 days post-discharge to check for resolution of AV block. Demographic characteristics, clinical characteristics, and complications during their hospital stay were evaluated. Major complications including respiratory failure requiring oxygen supplementation and mechanical ventilation, sepsis, deep vein thrombosis, elevated troponins, hospital and intensive care unit (ICU) length of stay, as well as death were compared between those who developed new onset AV blocks and those who did not. Results: Based on our single center study, the incidence of new onset AV blocks among patients admitted for COVID-19 during the study period was 5.5 cases per 100 patients. New onset AV blocks were not associated with longer hospital and ICU length of stay, increased intubation rates, or increased mortality. Conclusion: Although the development of a new onset AV block is most likely multifactorial and not solely due to COVID-19, it is still important for clinicians to be mindful about the possibility of developing symptomatic bradycardia and life-threatening arrhythmias in patients admitted for COVID-19. This can be achieved by appropriate rhythm monitoring in-patient but the need for a cardiac event monitor upon discharge is unlikely to be necessary. Careful history taking, including family and drug use history is also of great importance as emerging drug therapies for COVID-19 have potential arrhythmogenic effects. Graphical abstract: Image, graphical abstract